Losartan treatment improves recessive dystrophic epidermolysis bullosa: A case series. Issue 7 (29th April 2022) - Pourani, Mohammad Reza; Vahidnezhad, Hassan; Mansouri, Parvin; Youssefian, Leila; Rakhshan, Azadeh; Hajimoradi, Behzad; Abdollahimajd, Fahimeh; Uitto, Jouni
Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) manifests with blistering and erosions of the skin and mucous membranes due to mutations in COL7A1 . The repetitive wound healing processes lead to extensive cutaneous scarring. The scarring is driven by inflammatory processes, particularly the TGF‐β signaling pathways, resulting in excess synthesis and deposition of the extracellular matrix, especially collagen. There is currently no effective or specific treatment for RDEB. Losartan, an angiotensin II type 1 receptor antagonist, is an inhibitor of TGF‐β activity. Previous preclinical studies with hypomorphic Col7a1 mice recapitulating features of RDEB have suggested that losartan may improve the clinical features of RDEB. In this case series, we assessed the effects of losartan on the clinical and histopathologic features in seven patients with RDEB; three females and four males; aged 18.1 ± 9.1 years. The diagnosis was based on characteristic clinical features and the presence of biallelic loss‐of‐function mutations in COL7A1 . Daily oral administration of losartan (0.7 mg/kg) for six weeks resulted in subjective improvement of the clinical features, as judged by the treating physicians and the patients, and the severity of the disease objectively improved based on Birmingham Epidermolysis Bullosa Severity (BEBS) score (30.1 ± 12.8 versus 23.3 ± 10.4, before and after treatment, p = 0.018), accompanied by improvement of quality of life, as determined by the EB‐QoL questionnaire (24.0 ± 8.1 versus 17.7 ± 5.5, p = 0.018). Histopathology of the selected lesions revealed after treatment increased number of mast cells, and enhanced microvasculature in the mid and lower dermis. The width of collagen bundles in dermis was suggested to be decreased in four samples and changed from dense to loose in appearance. In summary, this case series reports beneficial effects of losartan on RDEB as a potentially novel treatment.